Comparison of the epidemiological characteristics of mycoplasma pneumoniae infections among children during two epidemics in Wuhan from 2018 to 2024 - Jieyu Mao; Zhili Niu; Mengling Liu; Liangyu Li; Haiyue Zhang; Ruiyun Li; Pingan Zhang; Xiaojun Wu (BMC Pediatrics)
Abstract Background Mycoplasma pneumoniae (M pneumoniae, MP) is a common pathogen causing respiratory tract infections, particularly in children. In 2023, a resurgence of MP epidemics was observed in Wuhan, Hubei Province, China. This study aims to examine the epidemiological trends and clinical characteristics of MP infections among children in Wuhan from 2018 to 2024, providing valuable scientific evidence to guide local prevention strategies. Methods From January 1, 2018, to June 30, 2024, samples were collected from children under 14 years with Acute Respiratory Tract Infections (ARTI) at Renmin Hospital of Wuhan University. MP infections were diagnosed through MP-IgM antibody detection and MP-DNA detection. Results were analyzed and compared across distinct epidemic periods. Results Of the 183 626 ARTI children, 57 393 (31.26%) tested positive for MP, with an average age of 4.87 ± 2.99 years and a male-to-female ratio of 1.12:1. The annual positive rates from 2018 to 2024 were 45.92%, 32.23%, 22.84%, 16.22%, 16.26%, and 42.93%, respectively. Across the study period, the highest positive rate was recored in autumn (35.13%, P < 0.05). Two distinct MP outbreaks were identified, in 2018–2019 and 2023. Significant differences were observed between the two outbreaks. The 2018–2019 epidemic peaked in summer, while the 2023 epidemic peaked in November and persisted into February 2024. By age, the 2018–2019 outbreaks predominantly affected pre-school children, whereas the 2023 outbreaks mainly involved school-aged children. In boths outbreaks, girls had higher positive rates. Antibody and DNA testing results followed similar trends. Conclusion This study highlights the epidemiological trends and clinical characteristics of MP infections in Wuhan from 2018 to 2024, including two distinct outbreaks with differing seasonal patterns. The MP strain in 2023 appeared to predominantly affect older children.The trends observed suggest that MP infections may persist into the winter of 2024. Enhanced surveillance of respiratory pathogens and early diagnosis and prevention of MP infections in children remain critical in this region.